2018
DOI: 10.26463/rjms.8_2_6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reasons for Donor Deferral in a Voluntary Blood Donation Camp-a Pilot Study

Abstract: Background Selection of voluntary blood donors is of vital importance towards safe blood transfusion services. The donor is the life force of any blood bank and hospital in a blood donation program. Hence the insight into the various causes of donor deferral is very importantAim To evaluate the donor deferral rate and reasons for deferral of blood donation in a voluntary blood donation camp.Material and methods This is a cross sectional study conducted in a voluntary blood donation camp held at a Degree Colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…14 Joy S et al reported that low haemoglobin and low body weight as major cause of donor deferral which was done among the student donors. 2 Shrivastava et al in their study mentioned that transfusion transmitted diseases was another major cause of donor deferral which is in accordance to the present study. One donor was underage (<18 years) which was deferred similar to other studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…14 Joy S et al reported that low haemoglobin and low body weight as major cause of donor deferral which was done among the student donors. 2 Shrivastava et al in their study mentioned that transfusion transmitted diseases was another major cause of donor deferral which is in accordance to the present study. One donor was underage (<18 years) which was deferred similar to other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Donor screening and evaluation is a prerequisite for blood safety. 2 Accordingly, deferred donors are informed and counselled. The various reasons for deferral in the voluntary blood donation camp held during second wave of COVID-19 pandemic were analysed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However there are several reasons which disqualify individuals who volunteer to donate blood, these individuals are known as "deferred donors". 2 The process of donor selection based on criteria of subjecting donors to a questionnaire, haemoglobin testing before blood donation and physical examination, only those who meet the requirements qualify as blood donors. 3 Deferral maybe temporary or permanent depending on donating blood due to being suspected or confirmed of having a haematological disease, infectious disease or any other medical condition that will either influence the safety of blood or donors' own health.…”
Section: Introductionmentioning
confidence: 99%